Protecting Academic Freedom in Australian Higher Education Through the Imposition of Restrictions on Investigatory Suspension - Levine, Pnina; Smith, Leigh (2021)
Academic freedom has received considerable recent attention, most notably with the former Chief Justice of the High Court of Australia, Robert French AC, releasing a report containing a Model Code for the Protection of Free Speech and Academic Freedom in early 2019. Although the Model Code endeavours to ensure that academic freedom is protected, it is asserted that for it to adequately serve its purpose, additional legal safeguards in the form of reasonable university disciplinary procedures must exist to avoid arbitrary disciplinary measures being taken against academics. This article argues that for academic freedom to be sufficiently protected, appropriate protections must not only exist to protect an academic from arbitrary dismissal but also from arbitrary suspension. It analyses the disciplinary procedures contained in the Group of Eight university enterprise agreements at the time of writing and relevant cases such as Jin v University of Newcastle and Imberger v University of Western Australia to demonstrate that there currently is a risk of academic staff members being arbitrarily suspended by their universities as a consequence of an exercise of academic freedom. It proposes a model term to be incorporated into future enterprise agreements to supplement the Model Code and reduce this risk.